Confirmation of GmPPR576 as a fertility restorer gene of cytoplasmic male sterility in soybean. (16th August 2021) - Wang, Tanliu; He, Tingting; Ding, Xianlong; Zhang, Qiqi; Yang, Longshu; Nie, Zhixing; Zhao, Tuanjie; Gai, Junyi; Yang, Shouping
Abstract: In soybean, heterosis achieved through the three-line system has been gradually applied in breeding to increase yield, but the underlying molecular mechanism remains unknown. We conducted a genetic analysis using the pollen fertility of offspring of the cross NJCMS1A×NJCMS1C. All the pollen of F1 plants was semi-sterile; in F2, the ratio of pollen-fertile plants to pollen-semi-sterile plants was 208:189. This result indicates that NJCMS1A is gametophyte sterile, and the fertility restoration of NJCMS1C to NJCMS1A is a quality trait controlled by a single gene locus. Using bulked segregant analysis, the fertility restorer gene Rf in NJCMS1C was located on chromosome 16 between the markers BARCSOYSSR_16_1067 and BARCSOYSSR_16_1078. Sequence analysis of genes in that region showed that GmPPR576 was non-functional in rf cultivars. GmPPR576 has one functional allele in Rf cultivars but three non-functional alleles in rf cultivars. Phylogenetic analysis showed that the GmPPR576 locus evolved rapidly with the presence of male-sterile cytoplasm. GmPPR576 belongs to the RFL fertility restorer gene family and is targeted to the mitochondria. GmPPR576 was knocked out in soybean N8855 using CRISPR/Cas9. The T1 plants showed sterile pollen, and T2 plants produced few pods at maturity. The results indicate that GmPPR576 is the fertility restorer gene of NJCMS1A. Abstract : We confirmed GmPPR576 as a fertility restorer gene of soybean CMS line NJCMS1A, which will enable more efficient use of heterosis and potentially bring about a green revolution in soybean farming.